2016
DOI: 10.1016/j.jacl.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the associations of visceral adiposity, homeostatic model assessment of insulin resistance, and body mass index with lipoprotein subclass analysis in obese adolescents

Abstract: Background The relationship of lipoprotein particle subclasses to visceral adipose tissue area (VAT-area) in obese children has not been examined previously. Objectives The study aims were to compare the relationships of VAT-area, homeostatic model assessment of insulin resistance (HOMA-IR), and body mass index (BMI) with lipids and lipoprotein subclasses in obese adolescents, and to determine if these relationships vary by sex. Methods This cross-sectional study of obese adolescents (BMI≥95th percentile),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Another finding of the present study was the sex differences in LDL-and HDL-subclass PN profiles. In a previous study in obese adolescents, 24 the positive association between VAT and small HDL-PN was shown in males, but not in females, which is compatible with our results. Another study in healthy children demonstrated that insulin sensitivity is a determinant of small HDL-PN in black boys and girls, however, only in white boys.…”
Section: Discussionsupporting
confidence: 93%
“…Another finding of the present study was the sex differences in LDL-and HDL-subclass PN profiles. In a previous study in obese adolescents, 24 the positive association between VAT and small HDL-PN was shown in males, but not in females, which is compatible with our results. Another study in healthy children demonstrated that insulin sensitivity is a determinant of small HDL-PN in black boys and girls, however, only in white boys.…”
Section: Discussionsupporting
confidence: 93%
“…Increased ectopic fat deposition (liver and visceral compartments) are strong predictors of glucose intolerance and type 2 diabetes. Many, but not all studies 91,92 , indicate that ectopic fat accumulation in visceral and hepatic compartments is a more significant determinant of cardiometabolic health than overall BMI in adolescents 93,94 and adults 95 with obesity. Visceral and intra-peritoneal adipose depots may increase hepatic insulin resistance through the release of localized inflammatory mediators or as a direct substrate for the release of free fatty acids 90 .…”
Section: Childhood Obesity Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%
“…Gender differences have also been described in fatty acid metabolism, with women being more sensitive to the antilipolytic effects of insulin than men, resulting in a greater release of free fatty acids that contribute to the production of TG and TC 39 . This could explain the higher triglyceride levels found in girls, although TC levels did not differ from those of boys.…”
Section: Discussionmentioning
confidence: 99%